O movimento sindical durante o Estado Novo : estado actual da investigação - Marques, Helder Miguel (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
In this article, that establishes the ‘state of the art’ of syndicalism during Portugal’s New State, through the analysis of the sustaining principles of the corporative system, the author attempts to demonstrate how the national trade unions, as structures of that same system, never ceased to be weak institutions, with a limited capacity for action in a dictatorial political regime which placed work at the end of the corporative scale of values.